Simulation and symbolic thinking in equations representing change - Ambar Narwal; Emily R. Fyfe; Benjamin Motz (PLoS ONE, 2025)
Learning simulations can enhance conceptual understanding in numerous education contexts, like physics, chemistry, ecology, and more. This conceptual understanding is often expressed symbolically using equations, and students are assessed on their ability to accurately express their ideas using these equations. In the current study, we explore how simulations can facilitate symbolic thinking, and specifically, how the presentation format of a simulation affects symbolic thinking in physics. Sixty-one undergraduate participants were assigned to one of three conditions: Animated Simulation, Textual Simulation and Control. In both simulation conditions, participants completed a set of tasks by manipulating values of key variables and observing changes in situations. These variables were speed, acceleration and time, and they influenced the motion of a ball in one dimension. While the Animated condition used animation of a moving ball to reflect these changes, the Textual condition reflected these changes through a structured text. No simulation was present in the Control condition. Participants then identified the equation which best described the situation. Compared to the Animated and Control conditions, participants in the Textual condition were more likely to identify the correct general form of the equation, where change was expressed through an addition term. These results highlight the importance of Textual simulations for equations describing one dimensional motion in physics.